CORE-MANTLE RELATIVE MOTION AND COUPLING - Vanyo J.P. (My University, 2004)
Core motion induced by lunisolar precession of the mantle is analysed and compared with experiments and Earth observations. First-order motion has the core axis lagging the mantle axis in precession by a small angle. This misalignment of the axes results in core-mantle relative velocities and displacements over the core-mantle interface as second-order flow. A third-order flow seen in experiments consists of nested fluid cylinders concentric with the core axis. First-order motion can be compared with westward drift and energy dissipation. Second-order motion can be compared with Earth observations using geomagnetic data, although its complexity may require numerical studies for detailed analysis. A specific lag angle and corresponding surface motions are suggested for comparison with Earth data leading to an apparent need for magnetic coupling between the core and the mantle.
Keywords: CORE ENERGY; CORE-MANTLE COUPLING; EARTH'S CORE; GEODYNAMO; PRECESSION